Integrasi Prinsip Keadilan Restoratif dalam Proses Perdata: Sebuah Pendekatan Baru Penyelesaian Sengketa: Menawarkan Model Penyelesaian Sengketa Berbasis Pemulihan Hubungan Sosial - Astri Anggraeni Putri; Sidi Ahyar Wiraguna (Parlementer : Jurnal Studi Hukum dan Administrasi Publik, 2025)
Indonesia’s civil dispute resolution system remains dominated by an adversarial litigation model that prioritizes legal certainty but often neglects the relational and emotional dimensions underlying conflicts. Yet, in many cases such as family, inheritance, or neighborhood disputes the restoration of social relationships is as crucial as formal legal resolution. This study explores the potential integration of restorative justice principles into Indonesia’s civil procedural law as an alternative approach centered on dialogue, accountability, and reconciliation. Employing a normative-juridical approach and qualitative analysis of primary and secondary legal sources, the research finds that restorative justice values align not only with Indonesia’s living law traditions such as musyawarah (deliberative consensus) and customary dispute resolution but also with existing provisions in civil procedure codes. Accordingly, the study proposes the Structured Restorative Mediation (SRM) Model, a procedural framework that embeds restorative principles into both court-annexed and community-based mediation. This model prioritizes relational healing while upholding legal certainty and procedural fairness. Its successful implementation requires regulatory support, enhanced mediator training, and institutional strengthening of community-based dispute resolution bodies. Thus, integrating restorative justice is not merely an innovation but a structural necessity for a more humane, inclusive, and holistically just legal system.